The phenomena of balanced effect between α-globin gene and of β-globin gene - Liangying Zhong; Xin Gan; Lingling Xu; Chujia Liang; Yingjun Xie; Wenbin Lin; Peisong Chen; Min Liu (BMC, 2018)
Abstract Background Thalassemias (TM) are the most common autosomal recessive disorders in Southeast Asian countries. Both α- and β-thalassemia lead to a decrease or absence of globin chains. The most serious of the thalassemia syndromes is thalassemia major which is characterized by a transfusion dependent anemia and subsequent iron overload caused by repeated blood transfusions. It is preventive by genotyping the parents. A better understanding of the laboratory data will help provide an accurate diagnosis of thalassemia major, and prevention and controlling programs in routine laboratories. Case presentation The patient was a one-year-old boy born to non-consanguineous parents. He was referred to our outpatient clinic for hemolytic anemia after a cold. Hematological investigations revealed severe anemia (Hb57 g/dL). The red cells displayed microcytosis, hypochromia and misshapen erythrocytes (MCV48.8 fL, MCH15.7 pg). Capillary electrophoresis (CE) electropherogram revealed normal level of HbA2 (3.2%) and elevated HbF (35.1%). The patient was diagnosed with β-TM, based on severe microcytosis, hypochromia, normal Hb A2 and high Hb F level but no Hb H inclusion at the first visit. Later our molecular analysis revealed compound heterozygosity for codons 41-42 (-TTCT) (HBB: c.126_129delCTTT, β0) and IVS-II-654 (C > T) (HBB: c.316-197C > T, β+) mutation and deletional Hb H (−-SEA/−α3.7). Thus, a combination of Hb H disease and a compound heterozygosity of β+/β0-thalassemia (β+/β0-thal) was finally diagnosed. Conclusions Genotype-phenotype analysis shows that heterozygous mutations in the β-globin gene could affect not only hematological parameters, but also elevate HbA2 levels. These effects could be ameliorated by the coinheritance of Hb H disease, which may be explained by the phenomena of the α-globin gene and of the β-globin gene balanced effect.